Transforming learning quality in elementary schools through the reflective action model in values-based instructional management - Seprie; Sri Wahyudi; Marheni Rayung Puspaningrum (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study investigates the implementation of the Reflective Action model within values-based instructional management to improve learning quality and character development in elementary education. The research examined how reflective cycles can enhance instructional management, student participation, academic achievement, and students’ character formation. A Reflective Action Research (RAR) design was employed through two iterative cycles consisting of planning, action, observation, and reflection stages. The study involved one fifth-grade classroom and one teacher, with data collected through observation sheets, student assessments, field notes, and teacher reflective journals. Data were analyzed using descriptive statistics and thematic analysis. The findings reveal consistent improvements across all variables from Cycle I to Cycle II. Instructional management became more structured and values-oriented, student participation increased significantly, and learning achievement improved, with mastery learning rising from 65% to 90%. In addition, character development indicators such as responsibility, discipline, cooperation, and respect also showed substantial improvement. The study concludes that reflective action integrated with values-based instructional management effectively enhances both academic and non-academic outcomes. The model contributes to educational practice by offering a systematic framework for continuous instructional improvement and holistic student development in elementary schools.